Analisis Minat Belajar Siswa Pada Materi KPK Dan FPB Menggunakan Pendekatan Saintifik Berbantuan Aplikasi Visual Basic Excel (VBE) - Neng Cucu Nurmaenah; Selvi Agini; Yulianda Putri; Siti Chotimah (Journal on Education, 2020)
This study aims to analyze the learning interests of Class IV Elementary students in learning mathematics on the KPK and FPB material assisted by the VBA Excel application by using 20 indicators of learning interest. The research method for analysis uses descriptive qualitative method, with the instrument used in the form of giving questionnaires containing positive and negative statements to analyze students' interest in learning mathematics. The sample subject in the study was grade IV Cibungur State Primary School located in West Bandung with the number of students 29 people. The results obtained from research that students' interest in learning mathematics learning aided by VBA Excel in the KPK and FPB material is good. Keywords: Analysis of interest in learning, VBA Excel